PERAN ASEAN MARITIME FORUM (AMF) DALAM MENJAGA KEAMANAN MARITIM (STUDI KASUS PEROMPAKAN DI PERAIRAN SELAT MALAKA) - Gaol, Trialen Lumban; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This Research is an ASEAN regional security study provides an analysis of the role of the ASEAN Maritime Forum (AMF) in maintaining maritime security is focused on cases of piracy in the Malacca Strait. Piracy is known as a violent act committed with the goal of having valuables of other people who do freelance sea or International Bodies and nationally. Where cases of piracy in the region of Southeast Asia, especially the Malacca Strait has increased from year to year, so piracy becomes an offense that requires the cooperation of ASEAN countries to eradicate this case.In this research uses the conceptual basis, with the concept of role (International Organisations) which here is AMF (ASEAN Maritime Forum), which is supervised by the organization of ASEAN as a regional organization that is still in contact area of the Straits. Backed by the International Organization level analysis and Theory of Constructivism, The concept leads to qualitative methods and library research for references.Some of the roles performed by the AMF is to be a forum for dialogue between ASEAN countries in resolving cases of piracy, increasing Capacity Building, as well as support the Confidence Building Measures (CBM) and Preventive Diplomacy and invite partners and the International Organization for keeping the Strait of Malacca and perform ngs meeting to discuss maritime security of Southeast Asia.Keywords: Piracy, Malacca Strait, AMF, Role, Security